Кредитна кооперація: проблеми та перспективи розвитку в Україні - Добровольська, Олена Володимирівна; Dobrovolska, Olena (Запорізький національний університет, 2017)
У статті визначено головні проблеми розвитку кредитної кооперації в Україні. Так, згідно з чинним законодавством України члени кредитної спілки не несуть відповідальність за її зобовʼязаннями. Гарантією виконання зобовʼязань має бути високий рівень договірної дисципліни, що досягається при укладанні договорів поруки з усіма членами спілки. Це забезпечує солідарну відповідальність перед спілкою за індивідуально отриманими кредитами. Отже, нарощування обсягів діяльності кредитних спілок та чисельності їх членів є умовою і результатом їх розвитку. Розвиток кредитної кооперації в Україні гальмується також затиснутістю діяльності кредитних спілок з боку законодавства, що не відповідає світовому досвіду та потребам практичної діяльності в сучасних умовах. Вузьким місцем є обмеження переліку господарських і фінансових операцій, які мають право здійснювати кредитні кооперативи. У звʼязку з цим актуальним є пропозиція надання можливості кредитним кооперативам здійснювати комерційні операції, що забезпечують фінансування їх основної статутної діяльності, та розвивати супутні види бізнесу, які зменшують ризики кредитування. На основі аналізу проблем системи кооперативного кредитування у вітчизняній економіці та передового світового досвіду іноземних країн розроблено рекомендації щодо удосконалення механізму його організації в перспективі. Основними напрямами розвитку кредитних спілок та посилення їх ролі на ринку фінансових послуг є: - зміцнення фінансової бази діяльності за рахунок формування територіальних обʼєднань кредитних спілок на обласному рівні та створення системи взаємної підтримки спілок; - координація діяльності кредитних спілок зі страховими організаціями; - співпраця з іншими ланками кооперативного сектора в аграрній сфері: виробничими та обслуговуючими кооперативами, споживчою кооперацією, зокрема участь кредитних спілок як структурних складових агропромислових формувань, що створені на кооперативній основі. The aim of the research is to identify the main problems of credit cooperation development in Ukraine and making some practical recommendations to improve the system of cooperative crediting in the future on this basis. The main problems of credit cooperation development in Ukraine have been defined in the article. Thus, according to the current legislation of Ukraine the members of the credit union are not responsible for its obligations. The obligation guarantee must be a high level of contractual discipline, which is achieved at making of security agreements with all members of the union. Thus, the growth of volumes of credit unions and the membership is a prerequisite to their development. According to the current legislation of Ukraine the members of the credit union are not responsible for its obligations. The obligation guarantee must be a high level of contractual discipline, which is achieved at making of security agreements with all members of the union. It provides solidarity liability to the union in case of individual loans. Credit cooperation development in Ukraine is also hampered by restraining activities of credit unions from legislation which does not meet the international experience and the needs of practical activities in modern conditions. The weak point is the limitation of the list of economic and financial transactions, which are entitled to carry out credit cooperatives. In this regard, topical is giving the opportunities to credit unions to carry out commercial operations, which ensure the financing of their primary statutory activity, and to develop related businesses that reduce credit risks. Based on the analysis of the problems of the cooperative crediting system in the national economy and the advanced world international countries developed recommendations to improve the mechanism of its organization in the future. The main directions of credit unions development and strengthening of their role in the market of financial services are: - strengthening of the financial base of activity due to the formation of territorial associations of credit unions at the regional level and the establishment of a system of mutual union support; - coordination of credit union activities of with insurance companies; - cooperation with other parts of the cooperative sector in the agricultural sector: production and service cooperatives, consumer co-operatives, particularly, participation of credit unions as structural components of the agricultural associations, established on a cooperative basis.
Credit cooperation: problems and prospects of development in Ukraine
Keywords: кредитна кооперація; credit cooperatives; кооперативне кредитування; cooperative crediting; кредитні спілки; credit unions; асоціація кредитних спілок; association of credit unions; кооперативний банк; cooperative bank